Evaluating the impact of bike-sharing services on Uber - evidence from New York city - Autz, David (2022)
This paper analyses the impact of bike-sharing services on ride-sharing services by using trip data in New York City during 2014 and 2015. The study works with datasets of Uber and Citi Bike, the two largest operators in their respective sectors. Using multiple linear regressions, the results show that both services can be seen as substitutes on a trip-by-trip basis. However, when widening the observational period and looking at the complete customer journey, this relationship is no longer significant. Moreover, trip duration and customer types play an essential role when quantifying the impact